Geology and geochemistry of granites in Panggong Lalat, Gua Musang, Kelantan - Muhammad Afif Aflah Mohd Yusri (2020)
The study area is located at Kampung Panggong Lalat, Gua Musang, Kelantan with the dimensions of 25 km2 of study area. These research paper objectives are to produce a geological map of the study area with the scale of 1:25000 and to investigate the rare earth element contents in granites of Panggong Lalat using petrographic and geochemical analysis method. The geological information in the study area is collected via geological mapping process. The lithology of the study area is consisted of granitoids, well-bedded limestone, volcanic rocks, fine-grained sediments and meta sedimentary rocks. The petrographic analysis is carried out in five different samples, AF 01, AF 03, AF 04, AF 06 and AF 07. The results showed three different types of granitoid by using JUGS Classification of igneous rock. AF 01 is quartz-rich granitoid, AF 04 is quartz alkali feldspar syenite and AF 03, AF 06 and AF 07 are alkali feldspar granite. For the geochemical analysis, two samples are chosen based on the difference in megascopic appearances. The result shows that the granite of the study area is of S-type granite. For ICP-OES analysis, the result shows that HREE distribution is richer than LREE with Er showing highest concentration value and Nd showing the least concentration value.